Faktor-Faktor Perilaku Konsumtif Mahasiswa Terhadap Produk Kosmetik Berlabel Halal - Maharani, Dewi; Masrina, Masrina; Aulia Putra, Ananda; Kalsum, Ummi (Yayasan Rahmat Islamiyah, 2024)
This research uses a quantitative research approach, using the independent variables price and religiosity, while the dependent variable is students' purchasing decisions. The results of this research can be concluded that there is a partial influence on the price variable (X1) on students' decisions (Y) on student decision variables in purchasing cosmetic products labeled halal. Meanwhile, simultaneously the variable price (X1) and religiosity (X2) on the decision variable (Y) of students in purchasing cosmetic products labeled halal have a significant influence. With a coefficient of determination (R Square) value of 0.553, this means that the variables price (X1) and religiosity (X2) influence students' decisions (Y) in purchasing cosmetic products labeled halal by 55.3% and the remainder is influenced by other variables.